Efeito do treino específico na habilidade de alcance manual em lactentes pré-termo - Guimarães, Elaine Leonezi (2013)
This study aimed to investigate the impact of a specific training (serial varied practice) of short duration on the performance of manual reaching in preterm infants, in the period immediately following the acquisition of this skill. For this purpose, the thesis consisted of three studies: Study 1, in which a systematic review of the behavior of manual reaching in preterm infants was conducted. Three independent reviewers participated in the selection and analysis of the selected articles. It was found that the manual reaching movement in preterm infants has still not been extensively described in the literature, indicating that there is much to learn about how prematurity associated with organic immaturity, and the extrinsic factors which influence the dynamics of this ability. In studies 2 and 3, for the assessment and training of reaching, infants were randomly divided into two groups: experimental and control. They were assessed positioned sitting reclined at 45° to the horizontal in a child seat up to 3 days after emergence of reaching. The experimental group underwent specific training (serial varied practice) for about five minutes and the control group was trained in social interaction in the same conditions for the same time. Two evaluations were performed, one pre- and one post-training, lasting two minutes each, for both groups. The assessments were recorded by three digital cameras, and the images were captured and analyzed using the Dvideow 5.0 videogrammetry system; Matlab 7.9 was used for the filtering of the results and the calculation of the kinematic variables of the study 3. Study 2, confirmed the influence of specific training on the frequency, in the proximal adjustments (uni-and bimanual) and distal adjustments (contact surface of the hand, palm orientation and opening of hand) of the manual reaching, in the period of emergence of the skill in preterm infants. The participants in the study were 18 infants of both sexes, born between 29 and 33 weeks of gestational age, with a birth weight less than 2500 grams, and who required postnatal hospital care. In the experimental group, the results after training showed a significant increase in the frequency of intragroup reaching (p=0.015) and between groups (p=0.026). There was significant difference in proximal adjustments, in the intragroup analysis, where after training the infants in the experimental group presented more unimanual (p= 0.025) and bimanual reaching (p = 0.023). In the intragroup analysis, the experimental group showed a significant difference in bimanual reaching (p=0.016) after training. Regarding distal adjustments apenas the experimental group displayed more reaching with the hand semiopen after training. A significant difference was noted in contact with the dorsal surface of the hand and fingers (p=0.027) and external oblique orientation (p=0.025). In the intergroup analysis there was a significant difference in opening of the hand (open, p=0.029), and in the orientation of the palm (external oblique, p=0.041) for the experimental group after training. Study 3 assessed the effect of specific training (serial varied practice) of short duration, on the kinematic variables (peak velocity, movement duration, mean velocity, straightness index, adjustment index, and movement unit) in manual reaching. It was found after specific training that only the experimental group showed a significant difference in peak velocity intragroup (p=0.036) and intergroup (p=0.016), which decreased after specific training, and the other variables showed no significant difference. However, according to the test that confirms the clinical relevance (Cohen's d), it was observed that after specific training (serial varied practice) of short duration, the experimental group showed a decrease in peak velocity, duration of movement, the number of movement units, and a slight increase in the rate of adjustment, indicating educational and clinical significance, suggesting that something has been learned and / or changed in the period immediately following the training session. The results indicate that specific training (serial varied practice) of short duration, favored more reaching with the external oblique, semiopen and open hand, with slower movement, with greater adjustment and fewest movement units in the period of acquisition, which may thus contribute to a better development and enhancement of this skill. Therefore, it is suggested that preterm infants may benefit from early practice (training), and this can be used as an intervention strategy for the acquisition, as well as the improvement of the reaching skill in the acquisition period, thus coming closer to the standard of mature reaching.